Search for an invisible scalar in tt¯ final states at the LHC - Azevedo, Duarte (2023)
We use the current tt¯ experimental analysis to look for Dark Matter (DM) particles hidden in the final state. We present a phenomenological study where we successfully perform the reconstruction of a tt¯ system in the presence of a scalar mediator Y 0, that couples to both Standard Model (SM) and to DM particles. We use a MadGraph5_aMC@NLO simplified DM model, where signal samples of pp → tt¯ Y 0 are generated at the Large Hadron Collider (LHC) with both Charge-Parity (CP) -even and CP-odd couplings of Y 0 to the top quarks. Different mass scales for the Y 0 mediator are considered, from the low mass region (~ 0 GeV) to masses close to the Higgs boson mass (125 GeV). The dileptonic final states of the tt¯ system were used in our analysis. The reconstruction of the tt¯ system is done with a kinematic fit, without reconstructing the mediator. All relevant SM backgrounds for the dileptonic tt¯ search at the LHC are considered. Furthermore, CP angular observables were used to probe the CP-nature of the coupling between the mediator and top-quarks, which allowed to set confidence level (CL) limits for those Yukawa couplings as a function of the mediator mass.